Prospective Mathematics Teachers’ Digital Literacy through Web-based Learning - Endang Cahya; Ratu Mauladaniyati; Nenden Suciyati Sartika; Krisna Satrio Perbowo; Wahyudin Wahyudin (International Journal on Emerging Mathematics Education, 2022)
This study aims to describe the digital literacy of prospective mathematics teachers who are conducting web-based learning in the new normal era. This research is classified as a qualitative descriptive research, data collected through surveys and interviews. The research subjects were 4th semester students of the mathematics education study program. Subjects were taken using purposive sampling technique for filling out the questionnaire and then 5 students were randomly selected to be interviewed. The results showed that the digital literacy of prospective mathematics teachers in web-based learning in the new normal era was quite good, this was evidenced by the results of student questionnaires which showed positive categories on each indicator. In addition, the cumulative percentage of students on the indicator of basic ability to use the internet (81.08%), on the indicator of the ability to seek and obtain information (75.32%), on the indicator of skills in choosing frequently used information sources (59.49%) and cumulative percentage of ability to use information effectively (81.87%). This is reinforced by the results of interviews with students which showed that the five students were able to achieve these four indicators.